Stock market wealth effects in an estimated DSGE model for Hong Kong - Michael Funke; Michael Paetz; Ernest Pytlarczyk (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
This paper develops and estimates an open economy dynamic stochastic general equilibrium (DSGE) model of the Hong Kong economy. The model features short-run price rigidities generated by monopolistic competition and staggered reoptimisation. The model is enhanced with wealth effects due to stock price dynamics, which we believe to be important. For this reason we adopt a perpetual youth approach. Model parameters and unobserved components are estimated with a Bayesian maximum likelihood procedure, conditional on prior information concerning the values of parameters.
URN:NBN:fi:bof-201408072196
Keywords: 330